2018
DOI: 10.1016/j.cellimm.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and lipid metabolism

Abstract: HighlightsThe transcriptional signature of Kupffer cells & Alveolar macrophages are enriched for lipid metabolism genes.Lipid metabolism may control macrophage phenotype.Dysregulated lipid metabolism in macrophages contributes to disease pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
273
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(284 citation statements)
references
References 212 publications
(324 reference statements)
10
273
0
1
Order By: Relevance
“…For example, M1 macrophages synthesize lipids and produce inflammatory lipid mediators like eicosanoids while M2 macrophages tend to take up and oxidize lipids. 34 This relationship appears in the context of obesity as well. Chawla et al demonstrated that the transcription factor peroxisome proliferator-activated receptor (PPAR) gamma is required for alternative activation of ATMs and that mice deficient in macrophage PPARγ have accelerated development of obesity and IR.…”
Section: Polarizationmentioning
confidence: 99%
“…For example, M1 macrophages synthesize lipids and produce inflammatory lipid mediators like eicosanoids while M2 macrophages tend to take up and oxidize lipids. 34 This relationship appears in the context of obesity as well. Chawla et al demonstrated that the transcription factor peroxisome proliferator-activated receptor (PPAR) gamma is required for alternative activation of ATMs and that mice deficient in macrophage PPARγ have accelerated development of obesity and IR.…”
Section: Polarizationmentioning
confidence: 99%
“…Macrophages ingest LDL, VLDL and oxidized lipoproteins becoming the classic foam cell. In dyslipidaemic states, such as with high levels of VLDL and LDL, excessive lipid uptake by macrophages is enhanced and together with defective cholesterol trafficking from the atherosclerotic lesion, promotes a pro‐inflammatory M1 macrophage phenotype and resultant accelerated atherogenesis . Pro‐inflammatory states frequently accompany a pro‐thrombotic phenotype as evidenced by increased platelet aggregation and a pro‐coagulopathic tendencies, as evidenced by increased levels of fibrinogen and plasminogen activator inhibitor‐1 …”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%
“…Consequently, it must be shuttled to the endoplasmic reticulum (ER) to be esterified and stored in lipid droplets, or effluxed from the cell via transporters such as the ATP-binding cassette transporter, ABCA1 (Remmerie and Scott, 2018). When there is too much free cholesterol in the ER the esterification machinery can become overwhelmed leading to the accumulation of free cholesterol, toll-like receptor (TLR) signaling, and nuclear factor kappa-light-chain enhancer (NF-kB) activation (Remmerie and Scott, 2018). This inflammatory signaling, combined with ER stress and the accumulation of free cholesterol, can cause cell death by apoptosis (Remmerie and Scott, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When there is too much free cholesterol in the ER the esterification machinery can become overwhelmed leading to the accumulation of free cholesterol, toll-like receptor (TLR) signaling, and nuclear factor kappa-light-chain enhancer (NF-kB) activation (Remmerie and Scott, 2018). This inflammatory signaling, combined with ER stress and the accumulation of free cholesterol, can cause cell death by apoptosis (Remmerie and Scott, 2018). Apoptotic macrophages must be cleared by neighboring macrophages which may themselves have stressed lipid metabolism and an impaired ability to perform this clearance function.…”
Section: Introductionmentioning
confidence: 99%